2022
DOI: 10.1007/s00520-022-07069-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an online home-based exercise intervention on breast cancer survivors during COVID-19 lockdown: a feasibility study

Abstract: Purpose The strict lockdown implemented due the COVID-19 pandemic is generating a great impact on wellbeing and health-related quality of life (HRQoL) in people with cancer. We aimed to evaluate the efficacy and feasibility of an online home-based exercise intervention performed during a lockdown period analysing its effects on body composition, physical fitness, and HRQoL in breast cancer survivors. Methods Fifteen women with breast cancer receiving hormonal therapy (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
4
32
1
Order By: Relevance
“…Implementation of the EXCEL study in the first year was also promising. Compared to previous work, EXCEL's exercise intervention adherence rate (78%; a range of 76-82% across regions) was lower than the adherence rates of recently published online exercise-oncology interventions of 86-91% [7,8]. However, the unique timing related to the COVID-19 pandemic was a critical factor.…”
Section: Methodscontrasting
confidence: 55%
See 2 more Smart Citations
“…Implementation of the EXCEL study in the first year was also promising. Compared to previous work, EXCEL's exercise intervention adherence rate (78%; a range of 76-82% across regions) was lower than the adherence rates of recently published online exercise-oncology interventions of 86-91% [7,8]. However, the unique timing related to the COVID-19 pandemic was a critical factor.…”
Section: Methodscontrasting
confidence: 55%
“…However, the unique timing related to the COVID-19 pandemic was a critical factor. Both prior studies [7,8] indicated that the online exercise interventions were completed during early lockdowns in the pandemic, potentially contributing to the increased adherence rates as participants had the time to exercise at home. This trend was observed in EXCEL, with the highest adherence rates being reported in earlier enrolment periods (Fall 2020 (84.3%) and Winter 2021 (84.4%)), whereas lower adherence rates were reported during periods in which lockdowns began to vary across regions (Spring (72.4%) and Fall 2021 (76.9%)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results con rm this statement since the BCS of the sample that trained in supervised programs had higher scores in all the HUNT1-PAQ variables, especially in intensity and duration of the sessions. In this regard, it is to be expected that, these BCS would obtain greater bene ts for the increased e ciency offered by this mode of training as other studies point out [26][27][28][29] even when such monitoring was carried out through supervised online programs during con nement [30][31][32] Finally, the main change observed comparing pre and post con nement periods was the change in the location where PA was performed, signi cantly increasing the BCS that preferred to train outdoors. Given that CS have a higher risk of infection [33,34] , it became necessary for them to modify their training habits in order to maintain their PA [33].…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility and effects of videoconference-delivered interventions to improve PA and other health outcomes among cancer survivors are still emerging (15). To our knowledge, only five studies have reported on videoconference-delivered exercise-oncology interventions or programs (16)(17)(18)(19)(20). Findings from these studies are promising in terms of feasibility, acceptability, and improvements in physical and psychosocial outcomes.…”
mentioning
confidence: 99%